An Insight Into Neonatal Cholestasis; A Tertiary Care Hospital Experience in Rawalpindi, Pakistan - Sughra Azhar; Farooq Ikam; Sarina Zainab Shirazi; Junaid Altaf; Rahmeen Pervaiz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequencies of various etiologies of neonatal cholestasis diagnosed by clinical findings and laboratory investigations at the Pak Emirates Military Hospital, Rawalpindi, Pakistan.